Sudden Death due to Diseased Intestines A case report of Crohn’s Disease - Malik, Yogender; Chaliha, Rituraj; Malik, Pushpendra; Jagdish, Rakesh Kumar; Sangwan, Kalpana; Rathee , Chavi (Journal of Indian Academy of Forensic Medicine, 2014)
Here we will present a case report of sudden, suspicious death of a truck handyman from Haryana who was on his way to Guwahati. He complained of fever and pain abdomen since last 2 days and was found unconscious in the morning after reaching Guwahati. External examination during autopsy did not reveal any injury. On opening the abdomen, multiple perforations in small and large intestines were found. Histopathology findings were found to be suggestive of Crohn’s disease, an inflammatory bowel disease (IBD). Crohn’s disease can affect any part of gastrointestinal tract and is rare in Asia but its incidence is increasing now. Peak age of onset of IBD is 15-30 years and a 2nd peak b/w 60-80 years. Highest mortality in IBD patients is during 1st years of disease. Intestinal perforations are known cause of sudden deaths but Crohn’s disease causing perforations is a relatively rare entity in our country, India.